Sub‐50 nm Channel Vertical Field‐Effect Transistors using Conventional Ink‐Jet Printing. Issue 4 (18th November 2016) - Baby, Tessy Theres; Rommel, Manuel; von Seggern, Falk; Friederich, Pascal; Reitz, Christian; Dehm, Simone; Kübel, Christian; Wenzel, Wolfgang; Hahn, Horst; Dasgupta, Subho
Abstract : A printed vertical field‐effect transistor is demonstrated, which decouples critical device dimensions from printing resolution. A printed mesoporous semiconductor layer, sandwiched between vertically stacked drive electrodes, provides <50 nm channel lengths. A polymer‐electrolyte‐based gate insulator infiltrates the percolating pores of the mesoporous channel to accumulate charge carriers at every semiconductor domain, thereby, resulting in an unprecedented current density of MA cm −2 .